Epidemiologic Impacts in Acute Infectious Disease Associated with Catastrophic Climate Events Related to Global Warming in the Northeast of Mexico - Santos Guzmán, Jesús; González Salazar, Francisco; Martínez Ozuna, Gregorio; Jiménez, Victor; Luviano, Andrea; Palazuelos, Daniel; Fernández Flores, Rubinia Iveth; Manzano Camarillo, Mario Guadalupe Francisco; Picazzo Palencia, Esteban; Gasca Sánchez, Francisco Manuel; Mejía Velázquez, Gerardo Manuel (Molecular Diversity Preservation International, 2021)
Rising global temperatures and seawater temperatures have led to an increase in extreme weather patterns leading to droughts and floods. These natural phenomena, in turn, affect the supply of drinking water in some communities, which causes an increase in the prevalence of diseases related to the supply of drinking water. The objective of this work is to demonstrate the effects of global warming on human health in the population of Monterrey, Mexico after Hurricane Alex. We interpolated data using statistical downscaling of climate projection data for 2050 and 2080 and correlated it with disease occurrence. We found a remarkable rise in the incidence of transmissible infectious disease symptoms. Gastrointestinal symptoms predominated and were associated with drinking of contaminated water like tap water or water from communal mobile water tanks, probably because of the contamination of clean water, the disruption of water sanitation, and the inability to maintain home hygiene practices.